An investigation of the factors relating to attendance of psychological appointments : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Auckland, New Zealand - Yelavich, Brooke (Massey University, 2021)
Background Psychological therapy is an important tool to improve mental health concerns. However, the high prevalence of mental health concerns is not reflected by mental health service use. Many individuals who are referred to a service do not attend or do not complete therapy. Methods A quantitative cross-sectional survey design was used to investigate psychological and practical factors which may impact attendance of psychological appointments. The factors investigated included: therapy anxiety, safety behaviours, intrinsic motivation, stigma, fear of disclosure, cultural safety, and practical factors. One qualitative method using an open ended question at the end of the survey was used to elicit further factors beyond the main survey questions that may predict non-attendance. Following exclusions, 669 participants were included in the final sample from Australia, New Zealand, Canada and the United Kingdom. Results The results of the study found statistically significant relationships between non-attendance and the following factors: therapy anxiety, safety behaviours, intrinsic motivation and self-stigma. Among the practical factors investigated, three of the 12 factors demonstrated statistically significant relationships with non-attendance these included, part-time employment, forgotten appointments, and family commitments. The results of the qualitative analysis highlighted five main categories of factors identified by participants. These categories included: psychological factors, practical factors, clinical factors, other commitments, and service factors. Conclusions Of the factors investigated in this study, therapy anxiety was the strongest psychological predictor of not attending therapy across the statistical models. Furthermore, therapy anxiety was one of the most self-reported reasons for not attending psychological appointments. While therapy anxiety was the strongest predictor, the study demonstrated a range of factors which related to individuals’ likelihood of attending psychological appointments. The findings of the current study may suggest that interventions that target a range of the most commonly identified factors would be more effective than trying to target just one of the various factors that cause non-attendance.
Keywords: Psychotherapy; Medical appointments and schedules; Psychotherapy patients; Psychology; 520302 Clinical psychology